A organização do trabalho pedagógico e currículo nos anos finais do ensino fundamental da Educação do Campo de Uruará, Pará - SILVA, Laurilene Matos da (2022)
Despite advances in legislation and public policies in the area of education, rural schools still do not meet the specific needs of people who live and work in the countryside. The objectives of this study are to discuss the organization of pedagogical work and the school curriculum in the final years of elementary school adopted for rural education in the municipality of Uruará, Pará, and to make notes for the construction of a pedagogical proposal for rural schools. This is a case study of a qualitative nature that was based on the speeches of three teachers working in the classroom, five students from the 6th to the 9th grade, one of the supervisors of the field classes and the director of EMEF Sistema Objetivo de Ensino. Data collection was carried out through interviews and took place in November of the year 2021. It was found that in the researched school there are gaps to be filled in terms of pedagogical work, lacking more assistance in teaching resources, monitoring in methodological procedures and specific training for teachers. The curriculum does not differ from that offered in the urban area, as well as the calendar, which is not geared to meet the particular demands of the countryside. Furthermore, there is a lack of a political pedagogical project that expresses the reality of the school community. Thus, suggestions were proposed for a proposal that allows the autonomy of the subjects, in thinking and acting as legitimate citizens and peasant citizens. It is concluded that field education and its methodological applications in the researched locus are not yet sufficiently materialized.